2018
DOI: 10.1177/1744806918769426
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of pro-inflammation signal pathway in inhibitory effects of rapamycin on oxaliplatin-induced neuropathic pain

Abstract: BackgroundOxaliplatin is a third-generation chemotherapeutic agent that is commonly used to treat metastatic digestive tumors; however, one of the main limiting complications of oxaliplatin is painful peripheral neuropathy. The purpose of this study was to examine the underlying mechanisms by which mammalian target of rapamycin (mTOR) and its signal are responsible for oxaliplatin-evoked neuropathic pain.MethodsNeuropathic pain was induced by intraperitoneal injection of oxaliplatin in rats. ELISA and Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…24) In addition, lacking of blood-brain-barrier makes peripheral nervous system more susceptible to the injury of chemotherapeutic accumulation like oxaliplatin, increasing the level of reactive oxygen species (ROS) and destroying the antioxidant-related proteins, and results in the disorder of redox balance in the end. 25,26) Moreover, the increase of ROS could attack the unsaturated fatty acids of nerve cells, then significant high levels of lipid peroxidation arise, resulting in the production of large amounts of MDA, so the level of MDA could be used as an indirect indicator of nerve cells' peroxidation. 27) While activation of antioxidant enzymes (SOD, GSH-Px and CAT) could reflect the elimination of ROS to a certain extent, [28][29][30] Liu and colleagues 31) and his team found that applicated antioxidant enzymes early could alleviate dysfunction of neurons, further confirmed the important role that oxidative stress playing in oxaliplatin-induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…24) In addition, lacking of blood-brain-barrier makes peripheral nervous system more susceptible to the injury of chemotherapeutic accumulation like oxaliplatin, increasing the level of reactive oxygen species (ROS) and destroying the antioxidant-related proteins, and results in the disorder of redox balance in the end. 25,26) Moreover, the increase of ROS could attack the unsaturated fatty acids of nerve cells, then significant high levels of lipid peroxidation arise, resulting in the production of large amounts of MDA, so the level of MDA could be used as an indirect indicator of nerve cells' peroxidation. 27) While activation of antioxidant enzymes (SOD, GSH-Px and CAT) could reflect the elimination of ROS to a certain extent, [28][29][30] Liu and colleagues 31) and his team found that applicated antioxidant enzymes early could alleviate dysfunction of neurons, further confirmed the important role that oxidative stress playing in oxaliplatin-induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Oxaliplatin-induced pain has also been shown to be accompanied with the upregulation of PI3K-mTOR and mTOR-mediated signals as well as IL-1β, IL-6, and TNF-α in DRG. As PI3K or mTOR signal was inhibited, mechanical and cold hypersensitivity were attenuated in oxaliplatin treated rats, and the levels of proinflammatory cytokines also decreased [38]. The upregulation of pro-inflammatory cytokines and membrane pro-inflammatory cytokine receptors in the midbrain periaqueductal gray, which has an inhibitory or excitatory control on pain transmission via the rostral ventromedial medulla, projecting to the spinal dorsal horn, of oxaliplatin treated rats is likely to impair the descending inhibitory pathways in regulation of pain transmission and thereby, contribute to the development of neuropathic pain after the administration of chemotherapeutic oxaliplatin [39].…”
Section: Discussionmentioning
confidence: 99%
“…Oxaliplatin (T0164, TargetMol) was dissolved in 5% GS to 2 mg/mL and intraperitoneally (IP) injected at a dose of 6 mg/kg to establish the neuropathic pain model [46]. The control group animals received a corresponding volume of 5% GS injection.…”
Section: Methodsmentioning
confidence: 99%